2020
DOI: 10.1186/s12909-019-1898-y
|View full text |Cite
|
Sign up to set email alerts
|

Peers as OSCE assessors for junior medical students – a review of routine use: a mixed methods study

Abstract: Background: Peer-assisted learning is well established in medical education; however, peer tutors rarely act as assessors for the OSCE. In the compulsory, near-peer teaching programme covering basic medical skills at the University of Heidelberg, peer tutors serve as assessors on a formative OSCE. This study aimed to investigate the feasibility and acceptance of peer assessors and to survey the perceived advantages and disadvantages of their use. Methods: In 2016 and 2017 all OSCE peer assessors (third to sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…This was recently emphasised in high volume classes expressing the reduction of costs with students giving feedback to a peer instead of teachers. 55 Nevertheless, students express the importance of clarifying the aim of the peer assessment activity and the responsibility of the faculty. We recommend faculty to clearly define the activity and explain how it supports student learning and professionalism, especially when students are to provide feedback to each other on sensitive matters, such as unprofessional behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This was recently emphasised in high volume classes expressing the reduction of costs with students giving feedback to a peer instead of teachers. 55 Nevertheless, students express the importance of clarifying the aim of the peer assessment activity and the responsibility of the faculty. We recommend faculty to clearly define the activity and explain how it supports student learning and professionalism, especially when students are to provide feedback to each other on sensitive matters, such as unprofessional behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Wie in der hier präsentierten Befragung sehen auch anderorts die Studierenden durchaus die Vorteile dieses Frageformats, wünschen sich aber insgesamt ausgewogene und sinnvoll eingesetzte Formate [29]. Neben aktuellen Bestrebungen im HeiCuMed zur Ausweitung der Verwendung von OSCE-Parcours [30] oder der Validierung von Key-Feature-Fragen [31] werden zukünftig auch weitere Anstrengungen nötig sein, um das Spektrum an innovativen und praktisch-orientierten Prüfungs-bzw. Prüfungsfragen-Formaten auszubauen.…”
Section: Reliabilität Und Notenverteilungunclassified
“…In recent years, peer assessment has been considered to be an effective learning strategy [ 2 ]. In a study of objective structured clinical examinations (OSCEs), peer assessment was found to be beneficial for learners, who received high-quality feedback and experienced stress reduction, and for peer assessors (PAs) in terms of improved teaching and clinical skills [ 3 ]. Basic life support (BLS) skills are a key element of the undergraduate curriculum that medical students should acquire.…”
Section: Introductionmentioning
confidence: 99%